A New Posterior Extensor Attachment-Point Reconstruction Technique for Cervical Spondylotic Myelopathy Involving C2 Segment: Clinical Outcome and Safety - Yang, Hai-Yun; Zhang, Yun-Ge; Zhao, Dong; Sun, Gui-Ming; Ma, Yi; Hao, Yong-Hong; Yang, Qiang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aim Cervical spondylotic myelopathy (CSM) is a common degenerative disease that mainly occurs in elder patients, leading to different degrees of neurological dysfunction. Spinal cord involvement is mainly distributed at the C3–C7 segments, but it may also involve up to the C2 level. This study aimed to assess the clinical efficacy and safety of open-door laminoplasty using a new extensor attachment-point reconstruction technique for treating CSM involving the C2 segment.Patients and Methods Fifty-nine patients with CSM involving the C2 segment and undergoing open-door laminoplasty were included in this retrospective study. Based on the titanium plate used in the operation, patients were divided into two groups, a reconstructed titanium plate fixation (RPF) group (n = 28) and a conventional titanium plate fixation (CPF) group (n = 31). Improvements in neurological function, cervical range of motion (ROM), cervical curvature index (CCI), preservation of posterior cervical muscle mass, and axial symptoms were compared between the two groups.Results There were no significant differences in operative time and intraoperative blood loss between the groups (p > 0.05). The Japanese Orthopaedic Association (JOA) score significantly increased in both groups postsurgery (p < 0.05); the neurological recovery rate was similar between the two groups (64.1 ± 13.3% vs. 65.9 ± 14.7%, p > 0.05). There was no significant loss of cervical ROM in either group (p > 0.05). The anteroposterior dural sac diameter at the C2 level was significantly enlarged in both groups (p < 0.05). Alternatively, CCI was significantly reduced in the CRP group (p < 0.05) but unchanged in the RPF group (p > 0.05). The cross-sectional area of the posterior cervical muscles was also significantly reduced in the CPF group (p < 0.05) but maintained in the RPF group (p > 0.05). Finally, axial symptoms were more severe in the CPF group than in the RPF group (p < 0.05).Conclusion Laminoplasty is an effective surgical procedure for CSM involving the C2 segment. The reconstructed titanium plate achieved superior maintenance of cervical curvature and reduced both muscle atrophy and severity of axial symptoms compared with titanium conventional plates.
Keywords: cervical spondylotic myelopathy; open-door laminoplasty; titanium plate; axial symptoms